The Role of Parents and Teachers in Fostering Interest in Memorizing the Koran for Students in The New Normal - Ernita Ernita (Ruhama : Islamic Education Journal, 2021)
Learning for students in the new normal period requires the main role of parents and teachers. The role of both determines interest in memorizing the Qur'an for students in the new normal period. The purpose of this study is to determine the role of parents and teachers during tahfiz learning for students, the role of parents and teachers in an effort to foster interest in learning tahfiz students, forms of collaboration between parents and teachers in order to foster interest in learning tahfiz and the level of memorization of participants. Studied at MTsN 2 Pasaman. This research method is based on a descriptive qualitative approach. The results of the research in this thesis are determined by the level of knowledge, the presence of parents, and interactions. So, students who have parents with good insight into tahfiz knowledge, and are more at home, then the role of parents can be given in full in tahfiz learning. On the other hand, students who have parents with less knowledge or knowledge of tahfiz, and are busy working, have a limited role in their children's tahfiz learning activities. Parents provide encouragement, messages, advice, sanctions and rewards to their children. This is done in order to foster interest in learning tahfiz students who study at madrasas or at home. Therefore, parents have performed their roles as motivators, educators, discipline enforcers, and regulators or controllers. The role of parents depends on the level of knowledge and basic tahfiz, as well as the intensity of the meeting between parents and students in interacting while at home.